Study on Pore Structure and the Microscopic Mechanism of the Difference in Petrophysical Properties of Tight Sandstone: A Case Study of the Chang 3 Member of Weibei Oilfield, Ordos Basin - Tang, Ying; Lei, Jingchao; Dong, Haoran; Tan, Shihao; Ma, Duanyue; Zhang, Nan; Wang, Mingxian (Frontiers in Earth Science, 2022)
Tight sandstone reservoirs have complex pore-throat structures, and poor and large differences in petrophysical properties. In this study, taking the Chang 3 Member of Weibei Oilfield, Ordos Basin, China as an example, the microscopic mechanism of the differences in petrophysical properties of tight sandstone reservoirs was systematically studied by thin section observation, scanning electron microscope, whole rock X-ray diffraction and high-pressure mercury intrusion experiments. The research results show that the reservoir types of the Chang 3 Member are mainly feldspar lithic sandstone and lithic feldspar sandstone; the pore types include intergranular, intragranular dissolution pores and a small amount of residual intergranular pores. Taking the permeability of 0.3 × 10-3 μm2 and 0.5 × 10-3 μm2 as the boundary, we divided the samples involved in high-pressure mercury intrusion into three categories according to the permeability from high to low: Type I, Type II and Type III. Their proportions were 31.4%, 20.0% and 48.6% respectively. The study found that the smaller the sorting coefficient, the poorer the petrophysical properties of the samples, and the pore-throat distribution of different samples gradually changed to a uniform double-peak-dominated type. The permeability of tight sandstone reservoirs is contributed by a small part of pore throats with large radius, while the reservoir space is mainly contributed by a large number of pores connected with small throats. The porosity is negatively and positively correlated with the median pressure and mercury injection tortuosity, respectively. In addition, the pore throat radius corresponding to the maximum permeability contribution rate, the maximum pore throat radius, and the sorting coefficient are all positively correlated with the permeability. In general, the areas with larger pore throat radius, lower pore throat tortuosity, and larger pore throat sorting coefficient can be regarded as favorable areas for Chang 3 tight sandstone reservoirs.